328 Translating to primary care physicians an effective safety program for parents of young drivers. (1st September 2016) - Shope, Jean; Zakrajsek, Jennifer; Finch, Stacia; Bingham, Raymond; O'Neil, Joseph; Yano, Stephen; Wasserman, Richard; Simons-Morton, Bruce
Abstract : Background: Crashes among US novice young drivers remain too high. Addressing this problem, one effective program for parents is Checkpoints, which raises parents' awareness of risks to their young drivers and offers ways to reduce those risks. But its most effective approach was in driver education classrooms and not widely available. A federally-funded study adapted Checkpoints to a website that could be promoted in several ways. This study promoted the Checkpoints website in brief interventions by Primary Care Practitioners (PCPs), and examined dissemination to/implementation by parents. Methods: The website, youngdriverparenting.org (with an interactive parent-teen driving agreement, PTDA), and brief intervention protocol were developed in collaboration with leadership of Paediatric Research in Office Settings at the American Academy of Paediatrics. PCPs delivered interventions and materials to parents, referred them to the website, and completed follow-up surveys. Google Analytics was used to assess parents' website use. Results: Focus groups of parents/teens determined the website adaptation successful. Most of the 133 PCPs from 16 states reported delivering interventions with fidelity, and thought the program important and feasible. Brief interventions/website referrals, averaging 4.4 minutes, were delivered to 3, 465 (87%) of 3, 990 eligible parents over an 18-week average in 2012–2013. Website visits (1, 453) were made by 42% of parents exposed to the intervention, who spent on average 3.53 minutes viewing an average of 4.2 pages. The PTDA was viewed by 24%, and 10% registered for an interactive PTDA. Conclusions: Translation of an evidence-based parent program to a PCP-promoted website was demonstrated. Delivering the brief intervention/website referral was feasible and acceptable to PCPs. This program costs little (its website, training and promotional materials are available) and could be one component of a comprehensive approach to reducing young driver crashes.